IL-23 signaling is not an important driver of liver inflammation and fibrosis in murine non-alcoholic steatohepatitis models - Jose E. Heredia; Clara Sorenson; Sean Flanagan; Victor Nunez; Charles Jones; Angela Martzall; Laurie Leong; Andres Paler Martinez; Alexis Scherl; Hans D. Brightbill; Nico Ghilardi; Ning Ding (PLoS ONE, 2022)
Non-alcoholic fatty liver disease (NAFLD), represents an unmet medical need that can progress to non-alcoholic steatohepatitis (NASH), which, without intervention, can result in the development of cirrhosis and hepatocellular carcinoma (HCC). Inflammation is a pathological hallmark of NASH, and targeting key inflammatory mediators of NASH may lead to potential therapeutics for the disease. Herein, we aimed to investigate the role of IL-23 signaling in NASH progression in murine models. We showed that recombinant IL-23 can promote IL-17 producing cell expansion in the liver and that these cells are predominately γδ T cells and Mucosal Associated Invariant T cells (MAITs). Reciprocally, we found that IL-23 signaling is necessary for the expansion of γδ T cells and MAIT cells in the western diet (WD) diet induced NASH model. However, we did not observe any significant differences in liver inflammation and fibrosis between wild type and Il23r-/- mice in the same NASH model. Furthermore, we found that Il23r deletion does not impact liver inflammation and fibrosis in the choline-deficient, L-amino acid-defined and high-fat diet (CDA-HFD) induced NASH model. Based on these findings, we therefore propose that IL-23 signaling is not necessary for NASH pathogenesis in preclinical models and targeting this pathway alone may not be an effective therapeutic approach to ameliorate the disease progression in NASH patients.